Synopsis of Canthiumera and Pyrostria (Rubiaceae, Vanguerieae) in Thailand - Duyfjes, Brigitta E.E.; De Wilde, Willem J.J.O.; Winkel, Esmée L.C.; Phonsena, Phongsak (Thai Forest Bulletin (Botany), 2023)
Canthiumera and Pyrostria comprise two species each in Thailand; three lectotypes are designated.